Biology Assessment Survey of Semarang Senior High As a Description of 21st Century Teacher’s Readiness (Journal of Innovative Science Education, 2020)
Critical thinking and problem solving skills, creativity and innovation, collaboration, and communication are types of skills that students must master to face the challenges of the 21st century. The role of the teacher in the learning process becomes an important factor to facilitate students in achieving the various skills needed at this time. The objectives of this study was to describe the readiness of 21st century teachers through the application of 21st century assessments, assessment quality, and alternative assessment models that lead to the needs of 21st century education. This research was conducted by surveys at six different schools, each involving six participant teachers and three participating students, using a quantitative non-experimental descriptive method. The results showed that the type of assessment used were varied, there were three participant teachers who have validated their Biology assessments through teacher discussion forums, and alternative assessment models used by participant teachers have not been used in their entirety, so the objectives of the assessment were not achieved. Thus, based on the Biology assessment used by high school teachers who were active participants in the Semarang MGMP group, it can be concluded that the majority of teacher in Semarang did not show readiness towards 21st century education needs, particularly in the application of assessments that lead to 21st century skills (4C's)